Legal Effects Incompatibility of the Principal Agreement with Additional Agreements - Zamirah, Rosita Linda; Adjie, Habib (Dinasti Research, 2025)
The provision of credit facilities by financial institutions and banking institutions is fraught with various risks, including defaults or non-payment by debtors. To anticipate such risks, lawmakers have provided creditors with general security facilities, as stipulated in Articles 1131 and 1132 of the Indonesian Civil Code. Under this general security, creditors are not given any special treatment in fulfilling their receivables. Consequently, creditors often feel that general security alone is insufficient. Therefore, creditors require debtors to provide specific collateral for debt repayment. The provision of such specific collateral is formalized in a security agreement made between the creditor and the debtor. This study aims to further examine the relationship between the principal agreement and the security agreement, as well as the legal consequences arising from a security agreement that does not conform to the principal agreement. The research adopts a conceptual approach and a statutory approach. Through this method, it can be determined that the security agreement must comply with the principal agreement as long as the parties do not agree otherwise or deviate from the applicable legal provisions. The explanation of Article 11, paragraph (1), No. 4 of the 1996 Mortgage Law